A geopoetic exploration of the Matinha vacant land, Lisbon - Paiva, Daniel (2019)
Our purpose in this communication is to present an exploration of the Matinha vacant land in Lisbon. Initially a sonic exploration, this endeavour would turn to the figure of the natural cyborg, an almost silent formation that thrives in the site, in the form of vegetal-technological hybrids.